Permafrost‒vegetation controls on water availability over the Qinghai‒Tibet Plateau - Fang Ji; Lin-Feng Fan; Shan-Shui Yuan; Xing-Xing Kuang; Liu-Jun Zhu; Jun-Liang Jin; Ying-Ying Yao; Jian-Yun Zhang; Chun-Miao Zheng (Advances in Climate Change Research, 2025)
Permafrost degradation substantially affects water resources within the cryosphere. It is crucial to elucidate the dynamics of water availability influenced by both permafrost degradation and climate change to fully comprehend the water cycle in cold regions, such as the Qinghai‒Tibet Plateau (QTP). While existing studies have established the hydrological consequences of permafrost degradation through altered soil hydraulics and water storage capacity, the complex interplay between thawing permafrost and vegetation dynamics—particularly their synergistic regulation of precipitation partitioning and runoff generation through root-zone water accessibility—are poorly understood, creating critical knowledge gaps in predicting long-term water availability trajectories. In this study, we explore the influence of permafrost-vegetation interactions on regional water availability on the QTP by integrating the effects of permafrost degradation on vegetation into the Budyko-Fu model. Our results reveal a consistent increase in surface runoff (R) of the permafrost regions from 1981 to 2100, predominantly driven by rising precipitation. However, shifts in vegetation patterns, prompted by permafrost degradation, significantly modify hydrological partitioning, leading to non-monotonic variations in the runoff to precipitation ratio (R/P). Notably, early-stage permafrost thaw enhances vegetation growth and evapotranspiration, which results in a decrease in R/P. Conversely, deeper permafrost thaw (e.g., beyond the root zone of vegetation) can lead to vegetation degradation, which subsequently reduces evapotranspiration and consequently increasing the R/P ratio. These findings underscore the pivotal role of vegetation in regulating the hydrological cycle and affecting water availability in permafrost-affected regions.